PERSEPSI PEGAWAI TERHADAP PENGAMBILAN KEPUTUSAN OLEH PIMPINAN PADA DINAS PENDIDIKANPEMUDA DAN OLAHRAGA KABUPATEN AGAM - Litdia Diana (Universitas Negeri Padang, 2013)
This study to obtain information on employee perceptions of the process, style and effectiveness of decision-making by the leadership at the Department of Education, Youth and Sports Agam. Thisis a descriptive study. Total population of 66 respondents sample taken is 53% of the total populationis 44 people. The technique used is Stratified Profertional Random Sampling Technique. Data collection tool used was a Likert scale. Thus it can be said that the employee perception of the Decision by the Chairman of the Department of Education Youth and Sports Agam is performing quite well (3.2). Kunci : Pengambilan Keputusan